2019
DOI: 10.1021/acs.jpcc.9b07702
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Physical Viewpoints About the Bonding in Fullerene–Graphene Hybrid Materials: Interaction on Pristine and Fe-Doped Graphene

Abstract: A DFT scheme was adopted to study the noncovalent/covalent attachment of fullerenes (C60, Si24C36, and B24N36) to graphene and Fe-doped graphene nanosheets (FeG). Geometrical, energetic, and electronic properties related to the physical and chemical nature of the bonding were characterized. The results show that fullerenes are physisorbed on graphene with adsorption energies of 0.7–1.2 eV, while the chemisorption is reached on FeG by cycloadditions with adsorption energies of 1.6–4.4 eV and is depending on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…6c-d system shows EELEC and EDISP contributions of 45 and 39%, respectively (major contribution of electrostatics, Fig. 5a); while the Graphene−C60 system is reported with EELEC and EDISP contributions of 33 and 67%, respectively (major contribution of dispersion) 40 .…”
Section: Interaction Mechanismmentioning
confidence: 95%
See 3 more Smart Citations
“…6c-d system shows EELEC and EDISP contributions of 45 and 39%, respectively (major contribution of electrostatics, Fig. 5a); while the Graphene−C60 system is reported with EELEC and EDISP contributions of 33 and 67%, respectively (major contribution of dispersion) 40 .…”
Section: Interaction Mechanismmentioning
confidence: 95%
“…As can be seen, Eads=0.9 eV for Phos−C60 complexes agrees with the experimental favorable non-covalent adsorption of fullerenes on phosphorene-based materials. Furthermore, the C60 adsorption stability increases at least 30% compared to related 2D materials such as graphene, where Eads0.7 eV is reported for Graphene−C60 non-covalent complexes [40][41][42][43][44] . Therefore, phosphorene serves as excellent support for fullerenes to form new hybrid nanostructures, ensuring a stable interaction.…”
Section: Structure and Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…[ 9–12 ] Literature reveals that 2‐D carbon materials emerge as ideal candidates for the adsorption of metal atoms, [ 13,14 ] gases, [ 15 ] neutral and charged clusters. [ 16,17 ] Recently, graphdiyne nanosheets are reported for the adsorption of different compounds. [ 18–22 ] For example, Srimathi et al [ 18 ] theoretically reported the affective use of graphdiyne as a biosensor material by adsorbing regorafenib drugs.…”
Section: Introductionmentioning
confidence: 99%